Expectation and perception of postgraduate students for service quality in UTM - Mohamad Tahar, Effaziela (2008)
Service quality has become predominant part of all advanced organizationâ€™s strategic plan. Higher attention on service quality has resulted in increasing and profit or an organizations. Higher education has possesses all the characteristics of service industry such as tangible, reliability, responsiveness, assurance and empathy. One characteristic of service quality was added for higher education which is information resources. The main aims of this study were to examine the expectation and perception towards service quality delivered by School of Graduate Studies (SPS) and analyze the gap between expectation and perception using the gap analysis. Using the modified SERVQUAL as a measure, this study asked postgraduate students during 2007/2008 academic session in Universiti Teknologi Malaysia to complete a service quality survey to compare their perceptions and expectations. Therefore, gaps in educational service quality at the higher education can be measured. A comparison of mean expectation scores to mean perception scores revealed a statistically significant relationship using Cronbachâ€™s coefficient alpha. The finding shows high reliability to all items in the modified questionnaires. This indicated that gap scores, as produced by this scale are valid measurement for overall satisfaction of postgraduate students with the delivery of services by the university. The result also showed that the gap of all dimension of service quality were negative. â€œResponsivenessâ€? and â€œempathyâ€? were identified as the most critical dimension for the School of Graduate Studies (SPS). Thus, improvements are required across all six dimension of service quality especially â€œresponsivenessâ€? and â€œempathyâ€?.